Deteksi Dini Resiko Tinggi Pada Ibu Hamil melalui program “Kemilau Penari”gi Pada Ibu Hamil melalui program “Kemilau Penari” - Wuri Widi Astuti (STIKES dan AKZI Karya Husada Kediri, 2022)
Pregnancy is a physiological condition and has great meaning in every woman's life. Although it is physiological in nature, the presence of diseases previously suffered by pregnant women or complications during pregnancy can cause complications for both the mother and the fetus in the womb. Therefore, it is necessary to make efforts to improve health, especially for pregnant women by detecting complications and high risks in pregnancy. The purpose of this activity is to improve education for pregnant women about early detection of high risks and complications in pregnancy by carrying out community service activities with the